Redes de colaboração científica: a dinâmica da rede em nanotecnologia - Oliveira, Saulo Campos (2011)
The scientific collaboration is one of the indicators to measure the development of research and progress in scientific discoveries. Serves, in other words, in conjunction with other indicators to measure and understand how science develops and direct investment in research. In this study area in particular, nanotechnology, the analysis of scientific collaboration network, converges to an alternative interpretation of the implementation of the Nanotechnology Brazilian Network. This study seeks to analyze the Brazilian scientific collaboration using the methodology of network analysis, together with the technique for generating bibliometric indicators of collaboration in the field of nanotechnology with data extracted from the database Web Of Science in the period 1998 to 2009. To guarantee this, it was necessary to experiment in different view settings for the network organization with the support of the representation of networks in specific software for Social Network Analysis (UCINET) and covalidation results with an expert participating in the network in search of information for the results obtained.These results show the comparison between the main actors of the network using the measures of Degree Centrality, Degree of Intermediation and Degree of Proximity evaluate the role and the relationship between authors and countries in terms of external collaboration and institutionsresearch and Brazilian states in terms of internal collaboration. It also pointed to the involvement of institutions of the State of São Paulo, especially UFSCar, this issue.Concludes by highlighting the importance of the use of methodological tools for evaluating the collaborative process of research and showing changes in the profile collaborative in the Nanotechnology in the analyzed period, which occurs in parallel with the implementation of the network in Brazil.